Nigerian children sexual abuse as a result of child labour - Mohd, Azizah; Amuda, Yusuff Jelili (Ontario International Development Agency, 2011)
Many Nigerian working children were the victims of sexual abuse as consequence and result of child labour across the nation. Some of them were raped, sexually abused by adult or peers due to the inadequate security to check and control crass act in society. This study examines the Nigerian provisions and rules against child sexual abuse and the gravity of punishment against the criminal whether such punishment capable and sufficient to serve the deterrent and lesson which are the purpose of punishment. The study further examines the punishment insight of Shariah to compare the best punishment to eradicate child sexual abuse across the nation. Both qualitative and quantitative methods were explored to discover undocumented facts and information on the subject matter. Useful suggestions were suggested in the best interest of child and nation at large.